Delivery of Bioactive Gene Particles via Gelatin-Collagen-PEG-Based Electrospun Matrices - Eleni K. Tsekoura; Teo Dick; Porntipa Pankongadisak; Daniel Graf; Yaman Boluk; Hasan Uludağ (MDPI AG, 2021)
The fabrication of fiber mats via electrospinning has been adopted in the last decades to produce high quality scaffolds for tissue engineering. However, an effective combination of electrospinning methods with gene delivery therapies remains a challenge. In this study, we describe how the delivery of gene complexes via electrospun mats that contain different volumes of gelatin (Gel), collagen (Col), and polyethylene glycol (PEG) can affect gene expression by transfected cells. Non-viral complexes were formulated by using lipid modified polyethylenimine (PEI) polymer and plasmid DNAs (pDNA) like the reporter Green Fluorescent Protein (GFP) and the therapeutically relevant Bone Morphogenetic Protein-2 (BMP-2) and electrospuned after being mixed with different volumes of Gel-Col-PEG mats and delivered to human myoblast (C2C12) and mouse osteoblast cells (MC3T3). The entrapment of GFP complexes via different homogeneous electrospun fiber mats revealed that a high fraction of collagen in the mats affected the quality of the fibers and led to reduced transfection efficiency on target cells. On the other hand, the fabrication of double-layered mats that contained collagen without complexes as a first layer and gelatin-collagen-PEG with complexes as a second layer successfully induced GFP expression and ALP activity in C2C12 cells. We conclude that this study has established the advantage of formulating multilayered bioactive collagen-based mats for gene delivery applications.